2014
DOI: 10.15252/embr.201338403
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for polyspecificity in the POT family of proton‐coupled oligopeptide transporters

Abstract: An enigma in the field of peptide transport is the structural basis for ligand promiscuity, as exemplified by PepT1, the mammalian plasma membrane peptide transporter. Here, we present crystal structures of di- and tripeptide-bound complexes of a bacterial homologue of PepT1, which reveal at least two mechanisms for peptide recognition that operate within a single, centrally located binding site. The dipeptide was orientated laterally in the binding site, whereas the tripeptide revealed an alternative vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
207
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(220 citation statements)
references
References 39 publications
12
207
1
Order By: Relevance
“…In a Ptr2 structural model based on the crystal structure of S. oneidensis PepT so (PDB 2XUT), a dipeptide is situated in a peptide-binding pocket that is surrounded by multiple amino acid residues, including R93, Y138, K205, and E480. Most recently, there was one substantive publication on structural issues with the substrate multispecificity of PepT st (44). The study presented crystal structures of di-and tripeptide-bound complexes of PepT st , which revealed that AlaPhe was oriented laterally in the binding site, whereas Ala-Ala-Ala showed an alternative vertical binding mode.…”
Section: Discussionmentioning
confidence: 99%
“…In a Ptr2 structural model based on the crystal structure of S. oneidensis PepT so (PDB 2XUT), a dipeptide is situated in a peptide-binding pocket that is surrounded by multiple amino acid residues, including R93, Y138, K205, and E480. Most recently, there was one substantive publication on structural issues with the substrate multispecificity of PepT st (44). The study presented crystal structures of di-and tripeptide-bound complexes of PepT st , which revealed that AlaPhe was oriented laterally in the binding site, whereas Ala-Ala-Ala showed an alternative vertical binding mode.…”
Section: Discussionmentioning
confidence: 99%
“…Insights into the biochemical basis for peptide binding and selectivity have recently come from three different POT family members crystallised in complex with peptides [17,34,35]. Detailed analyses of the binding interactions in these structures have been published recently [19,29] and will not be discussed in detail here.…”
Section: Peptide Binding and The Role Of Specificity Pockets In Liganmentioning
confidence: 99%
“…These two regions are opposite an acidic patch on TM7 and 10 in PepT St and a hydrophobic pocket, constructed of aromatic side chains from TM's 2, 11. Several lines of biochemical evidence suggest that ligand selectivity is the result of interactions between the side chains of the peptide and these pockets [34][35][36], which in turn promote the conformational changes required for transport. It is unclear what role, if any, symmetry plays in peptide recognition.…”
Section: Peptide Binding and The Role Of Specificity Pockets In Liganmentioning
confidence: 99%
“…Both the amino and the carboxy terminals are on the cytoplasmic side of the membrane. These proteins also contain potential sites in the intracellular loop for protein kinase-dependent phosphorylation (Chen et al 2002;Lyons et al 2014). The crystal structures of di-and tripeptide-bound complexes of a bacterial homolog of PepT1 revealed at least two mechanisms for peptide recognition.…”
mentioning
confidence: 99%
“…The crystal structures of di-and tripeptide-bound complexes of a bacterial homolog of PepT1 revealed at least two mechanisms for peptide recognition. The dipeptide was laterally oriented in the binding site, whereas the tripeptide revealed an alternative vertical binding mode (Lyons et al 2014). Molecular studies on the regulation of PepT gene expression in mammals indicates that the promoter of PepT1 has both an amino acid responsive element (Fei et al 2000) and binding sites for transcription factors, such as Cdx2, PPARα and Sp1 (Shiraga et al 1999).…”
mentioning
confidence: 99%